Anterior ST‐elevation myocardial infarction induced by rituximab infusion: A case report and review of the literature. (25th April 2017) - Sharif, K.; Watad, A.; Bragazzi, N. L.; Asher, E.; Abu Much, A.; Horowitz, Y.; Lidar, M.; Shoenfeld, Y.; Amital, H.
Summary: What is known and objectives: Rituximab is a chimeric monoclonal anti‐CD20 antibody approved for the treatment of some lymphoid malignancies as well as for autoimmune diseases including rheumatoid arthritis (RA), idiopathic thrombocytopenic purpura (ITP) and vasculitis. Generally, rituximab is well tolerated; nevertheless, some patients develop adverse effects including infusion reactions. Albeit rare, these reactions may in some cases be life‐threatening conditions. Rituximab cardiovascular side effects include more common effects such as hypertension, oedema and rare cases of arrhythmias and myocardial infarction. Case summary: In this article, we report a case of a 58‐year‐old man with a history of overlap syndrome including RA and limited scleroderma who was treated with rituximab and developed a dramatic ST‐elevation myocardial infarction (STEMI) during the drug administration. What is new and conclusion: This report underlines previous published reports emphasizing the awareness of such an association. This communication also warrants the importance of screening for ischaemic heart disease in selected cases of patients treated with rituximab. Abstract : Rituximab is a monoclonal antibody that is approved for treatment of certain malignancies and autoimmune diseases. Generally, Rituximab is well tolerated, nevertheless some patients develop adverse effects including infusion reactions. In this report, we investigated a patient who developed ST‐elevation myocardial infarction during the drug administration. Such complication albeit rare, can be fatal. This communication warrants the importance of screening for ischemic heart disease in selected cases of patients treated with rituximab.